Synchronous Collagenous Sprue and Enteropathy-Type T Cell Lymphoma: Variants of the Same Disease. (1st May 2004) - Medlicott, SAC; Beck, PL; Loken, S; Crabtree, T
Abstract : A 64-year-old man with treated hypothyroidism had 10 months of diarrhea, abdominal pain, anorexia and recent involuntary 13.6 kg weight loss. He presented to hospital with an acute abdomen that had a radiological correlate of free air under the diaphragm. He was diagnosed with a perforated mid-jejunum due to an ulcerated enteropathy-type T cell lymphoma (ETL), complicating collagenous sprue and cryptic celiac disease. Polymerase chain reaction verified monoclonal g- and b-T cell receptor gene rearrangements in the neoplasm. He had a complete resolution of symptoms when treated with a gluten-free diet in the postoperative period. This is apparently the first report describing collagenous sprue and ETL as synchronous lesions. Because atypical CD8+ lymphocytes are in both the collagenous sprue epithelium and ETL, the implication is that collagenous sprue is a noninvasive component of the ETL.